2018
DOI: 10.1016/j.ceramint.2018.08.349
|View full text |Cite
|
Sign up to set email alerts
|

Influence of random pore defects on failure mode and mechanical properties of SiC ceramics under uniaxial compression using discrete element method

Abstract: To investigate the relationship between micro defects in ceramic materials and macro mechanical properties and behaviours, a computational model of SiC ceramics with randomly oriented elliptical pores was established using the discrete element method (DEM). The effects of pore defect content and its aspect ratio on the failure mode, stress-strain curve and mechanical properties of specimen were investigated under uniaxial compression. The effective Young's modulus which was obtained from DEM simulations was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…A similar trend as with the effect of pore size is observed whereby the crack initiation temperature and the crack length increase with increasing pore aspect ratio. Although no experimental results for this specific parameter seem to be available in the literature, it is worth noting that, a similar type of behavior is reported for SiC ceramic materials in [50] using discrete element simulations under uni-axial compression. This observation is due to the fact that as the pore aspect ratio is increased, the stress concentration around the pores is increased leading to earlier crack initiation and increased total crack length.…”
Section: Effect Of Pore Aspect Ratiosupporting
confidence: 60%
“…A similar trend as with the effect of pore size is observed whereby the crack initiation temperature and the crack length increase with increasing pore aspect ratio. Although no experimental results for this specific parameter seem to be available in the literature, it is worth noting that, a similar type of behavior is reported for SiC ceramic materials in [50] using discrete element simulations under uni-axial compression. This observation is due to the fact that as the pore aspect ratio is increased, the stress concentration around the pores is increased leading to earlier crack initiation and increased total crack length.…”
Section: Effect Of Pore Aspect Ratiosupporting
confidence: 60%
“…7) include 22507 and 66743 disc particles, respectively. As the purpose of this study is to calibrate bond parameters, the deformation parameters and model size reported in [57,58] are directly adopted. The calibration methods for deformation parameters can be found in our recent work [22,23].…”
Section: Numerical Verificationmentioning
confidence: 99%
“…According to the fracture mechanics of hard-brittle materials, it can be known that the failure behavior of hardbrittle materials under complex load conditions is often caused by tensile failure, shear failure or mixed failure. In order to simulate the shear failure behavior of materials, researchers usually use compression test [21,42,69] to study the mechanical properties, and use this to calibrate the shear parameters in the micro-parameters. Concurrently, the tensile test [62], Brazilian test [16,70] or bending test [71,72] are usually used to study the tensile failure of materials, and to calibrate the tensile parameters in the micro-parameters.…”
Section: Validation Testsmentioning
confidence: 99%